Use of dried brewers' grains instead of soybean meal to feed lactating cows - Faccenda,Andressa (2017)
ABSTRACT The objective of this study was to determine the optimal level of dried brewers' grains (DBG) to replace soybean meal in diets for lactating Holstein cows. Five cows, around 88±28 days in milk, were distributed in a 5 × 5 Latin square design and fed diets containing different levels of DBG (0, 25, 50, 75, and 100%). The forage:concentrate ratio of the diet was 50:50. Feed intake, dry matter, nutrient digestibility, microbial synthesis, milk production and composition, and the economic viability of the diets were evaluated. There was reduction in dry matter intake and, consequently, in crude protein and non-fiber carbohydrates with increased levels of DBG. This occurred due to physical limitation of rumen caused by increased neutral detergent fiber intake. Ether extract intake also increased with levels of DBG due to higher concentrations of this nutrient in the diet. Apparent dry matter, organic matter, ether extract, and neutral detergent fiber digestibility increased with replacement of soybean meal by DBG. Milk production showed a quadratic effect and the levels of fat, protein, and total solids reduced linearly. Each 1% of soybean meal replaced by DBG in concentrate led to a reduction of 0.04, 0.02, and 0.06 g kg-1 of milk fat, protein, and total solids, respectively. The milk production efficiency increased linearly and the microbial synthesis efficiency was not affected. The economic return increased along with the DBG levels. Thus, DBG levels replacing up to 75% of soybean meal can be used to feed lactating cows, since it provides improvements in digestibility, milk production efficiency, and economic return without affecting microbial efficiency.